CALCULATION OF RADIONUKLIDA FORMATION ON ION CYCLOTRON SOURCE COMPONENTS - Silakhudin Silakhudin (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
This paper presents a prediction of radiation exposure on particle accelerator of cyclotron type that was began with calculation of radionuclides formationon ion source component has been done. The objectives of research are to identify the formation of radionuclides and probability of its radial distribution on ion source component. The methods of this research are to identify proton nuclear reaction with ion source component, determine of ion energy as radius function then converted to nuclear reaction cross section versus radius, and to determine the relation of ion beam transmission coefisient as function of radius. The probability of radionuclide formation can be determined with multiplying the reaction cross section and transmission coeffisient on certain radius. The result showed that the 65Zn and 63Zn radionuclides are important to be considered at the radius of several centimeters towards the extraction radius which location at maximum yields of radionuclides formation of 100% relatively on the radius of 36 cm and 38 cm respectively.